IMPLEMENTASI KEBIJAKAN SISTEM SATU ARAH PADA RUAS JALAN MAYOR ABDURAHMAN SUMEDANG - Arip Rahman Sudrajat; Nur Widia Pranawati; Nissa Sawitri (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2020)
This research on the Analysis of One-Way System Policy Implementation on Mayor Abdul Rahman Roads is motivated by traffic congestions that often occur on Jalan Mayor Abdul Rahman. In order to unravel that traffic congestions, the local government has made an effective traffic engineering policy. One of the efforts that can be done is to implement a one-way or one-way system policy on Major Abdul Rahman roads. From the preliminary data, it is known that the roads are congested. The implementation of this one-way system policy starts from the Pacific bridge to the Ojolali intersection. By implementing this one-way system policy, the government hopes to reduce the level of congestion on these roads. The research method used in the preparation of this report is descriptive method with a qualitative approach. The data obtained sourced from literature studies, field studies through activities such as observation, interviews, and documentation. In an effort to unravel congestion in the urban area of ??Sumedang, the Transportation Service (Dishub) of the Sumedang Regency Government carries out traffic engineering. The implementation of the one-way system policy is applied to the Major Abdul Rahman road section. On March 4, 2019, the Sumedang Regency government, supported by the Sumedang Police, carried out a traffic engineering trial to inform the public about the policies to be implemented. The traffic engineering trial was carried out around Jalan Mayor Abdurahman in the north and its surroundings. The implementation is guided by officers from the Sumedang Transportation Service and Police. One of the objectives of this traffic engineering is for the arrangement in the urban area of ??Sumedang.